Preventing bleeding and thromboembolic complications in atrial fibrillation patients undergoing surgery - Charles André (Arquivos de Neuro-Psiquiatria, 2015)
Neurologists feel uneasy when asked about temporary anticoagulant interruption for surgery in patients with atrial fibrillation (AF). Rational decisions can be made based on current scientific evidence. Method Critical review of international guidelines and selected references pertaining to bleeding and thromboembolism during periods of oral anticoagulant interruption. Results Withholding oral anticoagulants leads to an increased risk of perioperative thromboembolism, depending on factors such as age, renal and liver function, previous ischemic events, heart failure etc. Surgeries are associated with a variable risk of bleeding - from minimal to very high. Individualized decisions about preoperative drug suspension, bridging therapy with heparin and time to restart oral anticoagulants after hemostasis can significantly reduce these opposing risks. Conclusion Rational decisions can be made after discussion with all Health care team professionals involved and consideration of patient fears and expectations. Formal written protocols should help managing antithrombotic treatment during this delicate period.